2022
DOI: 10.3390/insects13020120
|View full text |Cite
|
Sign up to set email alerts
|

”Unmasking the Villain”: Integrative Taxonomy Reveals the Real Identity of the Key Pest (Thysanoptera: Thripidae) of Peanuts (Arachis hypogaea L.) in South America

Abstract: The peanut thrips, Enneothrips enigmaticus sp. n., is the key pest of Arachis hypogaea L. in South America, where it can cause yield losses of up to 85%. This species has historically been identified as Enneothrips flavens, but access to the holotype of this species and freshly collected material from southeastern and northern Brazil revealed that specimens commonly collected on peanut crops are not conspecific with E. flavens. Biological, molecular, and morphological assessments were carried out and led to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…Until now, there was only a record of E. enigmaticus associated with forage peanuts in Acre (Fazolin et al, 2015), which is considered the main pest of the peanut plants, A. hypogaea in Brazil (Lima et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, there was only a record of E. enigmaticus associated with forage peanuts in Acre (Fazolin et al, 2015), which is considered the main pest of the peanut plants, A. hypogaea in Brazil (Lima et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty rectangular pots were randomly inspected, and individuals were collected with a fine brush, counted, and placed in a bottle containing ethyl alcohol (70 %). Subsequently, the specimens were slide-mounted on glass slides and sealed with a cover slip in mounting medium following the methodology proposed by Mound and Marullo (1996) and identified based on Lima et al (2020Lima et al ( , 2022. Voucher specimens were deposited in the Natural History Collection of the Federal University of Piauí (CHNUFPI), municipality of Floriano, State of Piauí, Brazil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Thysanoptera groups are associated with forages. Most of them, such as Bregmatothrips Hood, 1912, Chirothrips Haliday, 1836and Plesiothrips Hood, 1915, are associated with Poaceae species (Mound 2011;Nakahara & Footit 2012;Mound et al 2016), and a few have been reported as occurring in or damaging legume pastures, such as Enneothrips enigmaticus Lima et al, 2022 (Thysanoptera: Thripidae) in Arachis pintoi Krapov & W.C. Gregory (Fazolin et al 2015;Lima et al 2022).…”
mentioning
confidence: 99%
“…The most commonly used species identification is by morphology, but molecular identification has become an ally with the barcode . Many species that were considered to be identical, with the barcode it was possible to identify that the genetic distance between these individuals was sufficient to classify them as different species (Bickford et al, 2007;Ashfaq & Hebert, 2016;Lima et al, 2022).…”
Section: Discussionmentioning
confidence: 99%